Chasing Ebola through the Endosomal Labyrinth - M. Javad Aman (American Society for Microbiology, 2016)
ABSTRACT During virus entry, the surface glycoprotein of Ebola virus (EBOV) undergoes a complex set of transformations within the endosomal network. Tools to study EBOV entry have been limited to static immunofluorescence or biochemical and functional analysis. In a recent article in mBio, Spence et al. reported a novel, live-cell-imaging method that tracks this transformational journey of EBOV in real time [J. S. Spence, T. B. Krause, E. Mittler, R. K. Jangra, and K. Chandran, mBio 7(1):e01857-15, 2016, http://dx.doi.org/10.1128/mBio.01857-15]. The assay validates known mechanisms of EBOV entry and sheds light on some novel intricacies. Direct evidence supports the hypothesis that fusion is a rare event that starts in maturing early endosomes, is completed in late endosomes, and occurs entirely in Niemann-Pick C1 (NPC1)-positive (NPC1+) compartments. The study demonstrated that lipid mixing and productive fusion are temporally decoupled, with different energetic barriers and a protease-dependent step between the two events. Analysis of the mechanism of action of an important class of EBOV neutralizing antibodies, such as KZ52 and ZMapp, provides direct evidence that these antibodies act by inhibiting the membrane fusion.